How transactive memory systems and reflexivity relate with innovation in healthcare teams - Marques-Quinteiro,Pedro (2019)
Transactive memory systems promote the effective exchange of diverse information, and may therefore contribute to healthcare teams innovation. Prior research on performance outcomes, however, suggests that transactive memory systems might be most useful for repetitive, rather than novel tasks. We reconcile these conflicting predictions by arguing that the information processing efficiencies of a transactive memory system will benefit innovation because transactive memory systems will help team members also reflecting on their processes and goals. We tested our hypotheses in a sample of 256 healthcare nurses (Nteams=54). Our findings support prior research showing that reflexivity is positively related to team innovation in teams. Furthermore, we found that reflexivity fully mediates the relationship between transactive memory systems and team innovation. This study contributes to the literature by addressing how team cognitive structures and processes combine to affect innovation. This study makes practical contributions by offering ideas for organizing in healthcare settings.